EFFICACY OF PLATELET-RICH PLASMA INJECTION VERSUS OXYGEN-OZONE THERAPY FOR THE TREATMENT OF KNEE OSTEOARTHRITIS : A META-ANALYSIS AND SYSTEMATIC REVIEW - Andika Prasetyo; Arimurti Pratianto; M. Yogi Alamsyah; Verika Christabela Tansuri (jfpublisher, 2025)
Introduction. Knee osteoarthritis (KOA), a degenerative knee condition, represents a major Indonesian public health issue because it consistently damages patients’ quality of life. Recent studies have explored the intra-articular injection of platelet-rich plasma and oxygen-ozone therapy as potential treatments for knee osteoarthritis. This review aimed to evaluate the effect of platelet-rich plasma (PRP) injection compared to oxygen-ozone therapy for treating knee osteoarthritis patients. Method. The reporting methodology of this work followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standards. A literature search was conducted through PubMed and Google Scholar by combining several keywords, including PRP Injection with oxygen-ozone therapy for patients affected by KOA. The Cochrane Risk of Bias 2 (ROB 2) tool was employed to assess the risk of bias. Result&Analysis. The meta-analysis included 251 participants from these 4 Randomized Controlled Trials (RCTs) the results indicated no statistically significant difference between PRP injection and oxygen-ozone therapy in terms of the visual analog scale score and the mean difference in the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain subscale at the 1-month follow-up. However, a significant difference was observed between the two interventions in the WOMAC subscales for stiffness and physical function. Discussion. This meta-analysis shows that KOA patients might achieve better pain relief together with improved function outcomes from PRP injections than from oxygen-ozone therapy based on joint stiffness and functionality WOMAC scores.